2017
DOI: 10.5194/acp-17-10405-2017
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing source fingerprints and ageing processes in laboratory-generated secondary organic aerosols using proton-nuclear magnetic resonance (<sup>1</sup>H-NMR) analysis and HPLC HULIS determination

Abstract: Abstract. The study of secondary organic aerosol (SOA) in laboratory settings has greatly increased our knowledge of the diverse chemical processes and environmental conditions responsible for the formation of particulate matter starting from biogenic and anthropogenic volatile compounds. However, characteristics of the different experimental setups and the way they impact the composition and the timescale of formation of SOA are still subject to debate. In this study, SOA samples were generated using a potent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…The specific fluorescence area was widened in the ambient sample and, thus, had a higher AFI/WSOC ratio when WSOC concentrations were at a comparable level. The continuous oxidation of organics may break up the π system of organics and extinct fluorescence (Zanca et al, 2017). It could be inferred that ambient WSOCs tended to exhibit higher AFI/WSOC ratios, whereas both freshly emitted WSOCs and completely oxidized WSOCs could lead to lower AFI/WSOC values.…”
Section: Discussionmentioning
confidence: 99%
“…The specific fluorescence area was widened in the ambient sample and, thus, had a higher AFI/WSOC ratio when WSOC concentrations were at a comparable level. The continuous oxidation of organics may break up the π system of organics and extinct fluorescence (Zanca et al, 2017). It could be inferred that ambient WSOCs tended to exhibit higher AFI/WSOC ratios, whereas both freshly emitted WSOCs and completely oxidized WSOCs could lead to lower AFI/WSOC values.…”
Section: Discussionmentioning
confidence: 99%
“…To establish photooxidation conditions, the O 3 was photolyzed at λ of 254 nm inside the OFR to generate O­( 1 D) radicals, which reacted with H 2 O to continuously produce hydroxyl (OH) radicals ([OH] ≈ 10 10 cm –3 ). Recent studies suggest that SOA particles generated in OFRs have compositions similar to SOA generated in environmental chambers , and in the atmosphere. …”
Section: Methodsmentioning
confidence: 99%
“…Another study reported increased RNA oxidation in cells exposed to SOA resulting in transcript alteration and cell function disruption . Some molecules namely cinnamic acid, hydroxybenzoic acid, and 1,4-naphtaquinone were found in SOA, and they or their derivatives have been reported to induce apoptosis and autophagy in multiples cancer cells lines. …”
Section: Pathogenic Impact Of Soamentioning
confidence: 99%